Blueberry Gall Midge, Dasineura oxycoccana (Johnson) (Insecta: Diptera: Cecidomyiidae) - Gary J. Steck; Paul M. Lyrene; J. A. Payne (EDIS, 2002)
This document is EENY-136 (originally published as DPI Entomology Circular No. 373), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000.